2007
DOI: 10.1080/17482940701534818
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mechanical cardiac assist in myocardial infarction. Where are we now, where are we going?

Abstract: Since its first clinical application in patients with cardiogenic shock (CS) in 1968, the intra aortic balloon pump (IABP) increasingly has been used for several clinical conditions requiring mechanical cardiac assistance. In current practice, IABP therapy is still the most accessible and most frequently used method of mechanical cardiac assistance. It is primarily being used as a therapeutic instrument for hemodynamic stabilization in left ventricular failure and cardiogenic shock, mainly in patients with myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Intra-aortic balloon counterpulsation is still the most used method of LV unloading and haemodynamic support in the catheterisation laboratory [5]. However, the use of IABP therapy concomitant to primary PCI remains controversial, due to lack of sufficient (randomised) scientific support, as evidenced recently by a meta-analysis from our group [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-aortic balloon counterpulsation is still the most used method of LV unloading and haemodynamic support in the catheterisation laboratory [5]. However, the use of IABP therapy concomitant to primary PCI remains controversial, due to lack of sufficient (randomised) scientific support, as evidenced recently by a meta-analysis from our group [10].…”
Section: Discussionmentioning
confidence: 99%
“…(nitric oxide synthase inhibitors), which lowered mortality [3,4]. With the development of new, perhaps more potent, mechanical cardiac assist devices, the role of IABP therapy in the management of CS in recent studies has again been of major interest [5][6][7][8][9]. Routine use of IABP therapy in the setting of high-risk STEMI is not supported by evidence from randomised trials, as shown in our recently published meta-analysis [10].…”
Section: Introductionmentioning
confidence: 99%
“…PCI and other indications were the high complication rates and complex handling of earlier devices, such as the femoro-femoral cardiopulmonary support system, Hemopump (Medtronic, Minneapolis, Minnesota), and the Tandemheart (CardiacAssist, Pittsburgh, Pennsylvania) (1,10). Three small series of periprocedural Impella 2.5 support were encouraging with respect to safety and feasibility (2,4,5).…”
mentioning
confidence: 99%
“…The need for a quick and effective assist has always been pushing us in these intense moments of struggle for the patient's life. An excellent review on the ''state-ofthe-heart'' of percutaneous cardiac assist for the treatment of myocardial infarction is given by Sjauw et al (4). The world of percutaneous ventricular assist has left its stagnant phase and is rapidly changing.…”
Section: Rafael Beyarmentioning
confidence: 99%